Inclusion complexes of chloramphenicol with β-cyclodextrin and aminoacids as a way to increase drug solubility and modulate ROS production. (5th May 2015) - Aiassa, Virginia; Zoppi, Ariana; Albesa, Inés; Longhi, Marcela R.
Graphical abstract: Highlights: Chloramphenicol multi-component complexes were prepared and characterized. The water solubility of chloramphenicol was improved. Chloramphenicol production of reactive oxygen species in leucocytes was decrease. The complexes maintain good antibacterial activities in vitro . Abstract: The aim of this study was to improve the solubility of chloramphenicol and reduce the production of reactive oxygen species (ROS) in leucocytes induced by this drug, using complexation. Multicomponent complexes were prepared by the addition of β-cyclodextrin with glycine or cysteine. Nuclear magnetic resonance and phase solubility studies provided information at the molecular level on the structure of the complexes and their association binding constants, respectively. In the solid state, all systems were extensively characterized by Fourier-transform infrared spectroscopy, scanning electron microscopy, thermal analysis and X-ray powder diffraction. Antimicrobial activity of inclusion complexes was investigated by agar diffusion methods. Finally ROS determination by chemiluminescence was used to investigate the effect of complex formation on the potential toxicity in human leucocytes. These studies revealed that multicomponent complexes can increase the aqueous solubility of chloramphenicol as well as reducing the stress by ROS production in leucocytes and maintaining its microbiological activity.